PENERAPAN MEDIA GAMES BLOOKET PADA MATA PELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV DI SDN 066050 MEDAN - Milenia Nainggolan; Feri Haryati; Zuraida Hanum Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the application of blooket games learning media to elementary school student learning outcomes. The research method used was fifth grade students of an elementary school at SDN 066050 Medan. This research focuses on the low mathematics learning outcomes in addition and subtraction of fractions in class V UPT SD Negeri 066050 Medan. The method used is Classroom Action Research (PTK). This proves that the application of Blooket Games learning media to student learning outcomes has a very good influence. The subjects of this research were 20 class IV students. Data collection was carried out through tests, and the results showed a significant increase in learning outcomes. After implementing the use of Blooket media games, this percentage increased to 50% in cycle I and reached 90% in cycle II. The average student score also increased from 62,75 in pre-action to 72,25 in cycle I, and 80,5 in cycle II. This proves that the application of the Blooket game learning media has a significant effect on student learning outcomes. In addition, students who study with Blooket show improved learning outcomes. These results indicate that game-based learning media can be an effective alternative for improving student learning outcomes.